‘Secular dialectic’ in depictions of sexuality of Prophet Muhammad in selected works of contemporary writers of Muslim descent - Mohamad Rosli, Ummi Nadhirah (2018)
For a long time, Prophet Muhammad’s (Sall Allahu ‘alayhi wa sallam) marital affairs have been the centre of criticism in the Western discourse of Islam. His multiple marriages were criticised by medieval polemicists and his marriage with Ayesha (radiya Allahu ‘anha) that only pervaded later in the discourse, painted an image of the Prophet (saw) as a leader driven by lust and sexual desires. It is with this particular concern of sexuality that Western writers inveigh against the merit of Muhammad (saw) as a moral figure and it is this particular concern that this study focuses on. The present study extends the research on the sexual representations in relation to the Prophet (saw) within the works of contemporary writers of Muslim descent. The works selected include the poems “The Woman who Said No” and “The Woman who Said Yes” by Malaysian poet Salleh Ben Joned, the novels The Satanic Verses by Indian writer Salman Rushdie and Banquet of Lies by Algerian author Amin Zaoui. The study is located in the bigger theoretical framework of secularisation where I situate the the oretical methodological aspect of the research in the notion referred to as the ‘secular dialectic’. The notion presents a dynamic in the relationship between Islam and secularisation that argues beyond their dichotomous categorisations, and instead, it demonstrates a process of mutuality between religious traditionalism and the secular discourse to produce alternative ideas of faith, ethics and identity. The notion is modelled from Homi K.Bhabha’s postcolonial concept of ‘Third Space’ and Charles Taylor secular concept of ‘cross-pressure’. These concepts share the view of a dialectical interaction between different cultural and religious systems and position postcolonial hybridity within the secular framework such as in the case of the selected writers who were born and raised in non-Western Muslim countries and whose exposures to the secular West contribute critically to the dialectical discourse. The analysis, therefore, examines the writers’ dialectical views based on their perspectives of Islam in modernity from their written prose as well as their aesthetic delivery of the dialectic through their depictions of the Prophet (saw) in light of sexuality. The study aims to investigate how a dominant Western imagery of Prophet Muhammad (saw) has infiltrated the works of the selected Muslim writers. The ‘secular dialectic’ suggests that sexual ideas associated to the Prophet (saw) are made possible through the concomitancy between the religious and secular discourses, but such process fundamentally panders to the predominance of Western secularisation that in the end questions the writers’ works. By using the Prophet’s (saw) image as a dialectical symbol, these works risk promoting a Western discourse that has dominated thoughts about Islam and the Prophet (saw), putting other Muslims in a position where their faith and identity are challenged in modern discourses while implicitly and continuously complicating the image of the last Prophet of Islam.